2018
DOI: 10.18502/kss.v3i6.2391
|View full text |Cite
|
Sign up to set email alerts
|

The Research Skills, Personal Effectiveness, Networking and Team Working, and Communication Skills of Polytechnic University of the Philippines Laguna Campuses Faculty: Basis for an Action Plan

Abstract: This study aimed to assess the Research Skills, Personal Effectiveness, Networking and Based on the findings, it was concluded that the respondents have a consensus that they are able to practice and demonstrate relevant research skills, they are able to work harmoniously and emphatically with their network and respective team in a collaborative effort. Thus, it was recommended that those teachers who are in their early years of teaching must be given support in terms of research training that will supplement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
2
1
Order By: Relevance
“…The present findings contradict Pambuena (2022), indicating that 91 members of the Polytechnic University of the Philippines' Laguna Local Government Campus faculty and staff had a "moderate" level of affective commitment. Similarly, in another study by Nitafan (Nitafan, 2020), the regular staff members of the local governments of Cabakan, Matalam, and Carmen, province of Cotabato, had a similar level of commitment.…”
Section: Level Of Organizational Commitment Among Employees In Cooper...contrasting
confidence: 97%
See 1 more Smart Citation
“…The present findings contradict Pambuena (2022), indicating that 91 members of the Polytechnic University of the Philippines' Laguna Local Government Campus faculty and staff had a "moderate" level of affective commitment. Similarly, in another study by Nitafan (Nitafan, 2020), the regular staff members of the local governments of Cabakan, Matalam, and Carmen, province of Cotabato, had a similar level of commitment.…”
Section: Level Of Organizational Commitment Among Employees In Cooper...contrasting
confidence: 97%
“…Both studies revealed that most participants had already developed a sense of attachment and belongingness and were willing to continue serving their organization. Also, Alipio (2020) Conversely, this study has a slight variation from that of Pambuena (2022) as the "moderate" level of continuance, and normative commitment was still present among 91 academic and staff members at the Polytechnic University of the Philippines -Local Government Campuses in Laguna, comparable to Nitafan (2020). However, both studies showed that most participants had a somewhat lower level of organizational loyalty and a sense of duty than cooperative employees in Zamboanga del Sur, who showed a higher level of normative and continuance commitment.…”
Section: Level Of Organizational Commitment Among Employees In Cooper...mentioning
confidence: 70%
“…Ulla (2018) cited insufficient research training (Ellis and Loughland, 2016) and lack of research skills (V asquez, 2017) as two of the "primary challenges and concerns faced by teachers and other educators aspiring to undertake research" (p. 797). Pambuena and Bernarte (2018) recommended in their paper that "early years of teaching must be given support in terms of research training" (p. 339). Though there are obstacles in using action research because it "add little to candidates' perceptions of their knowledge of content, instructional planning, teaching methods, and assessment" (Lattimer, 2012, p. 18), the findings above showed that the benefits outweigh the challenges so action research can prepare teacher education students to be effective teachers.…”
Section: Research Questionsmentioning
confidence: 99%